2020
DOI: 10.1007/s00442-020-04668-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fatty acid composition related to ontogenetic changes and niche differentiation of a common aquatic consumer

Abstract: Fatty acids (FAs) are key nutrients for fitness which take part in multiple physiological processes over the ontogeny of organisms. Yet, we lack evidence on how FA nutrition mediates life-history trade-offs and ontogenetic niche shifts in natural populations. In a field study, we analyzed ontogenetic changes in the FAs of Eurasian perch (Perca fluviatilis L.), a widespread fish that goes through ontogenetic niche shifts and can have high individual niche specialization. Diet explained most of the variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 68 publications
1
35
0
Order By: Relevance
“…In previous studies, we found that Eurasian perch ( Perca fluviatilis ) specializing on benthic invertebrates, a resource low in DHA, showed similar proportions of DHA in muscle tissue compared to perch feeding primarily on zooplankton of high-DHA content (Scharnweber et al 2016 ). Along the same line, Chaguaceda et al ( 2020 ) found that 72% of the fatty acid variation in perch remained unexplained by diet, suggesting that other factors, for example, bioconversion may also affect the fatty acid composition.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In previous studies, we found that Eurasian perch ( Perca fluviatilis ) specializing on benthic invertebrates, a resource low in DHA, showed similar proportions of DHA in muscle tissue compared to perch feeding primarily on zooplankton of high-DHA content (Scharnweber et al 2016 ). Along the same line, Chaguaceda et al ( 2020 ) found that 72% of the fatty acid variation in perch remained unexplained by diet, suggesting that other factors, for example, bioconversion may also affect the fatty acid composition.…”
Section: Introductionmentioning
confidence: 89%
“…In August 2015, we sampled perch from Lake Erken (59°50′09.6″N, 18°37′52.3″E) in Central Sweden which has been extensively studied with respect to dietary specialization (e.g. Chaguaceda et al 2020 ; Marklund et al 2019 ; Svanbäck et al 2003 ). Perch and potential prey fish (ruffe, Gymnocephalus cernua and roach, Rutilus rutilus ) were caught using multimesh gill nets (littoral nets: 30 × 1.5 m; pelagic nets: 27.5 × 6 m) that were set overnight, either in the shallow near-shore littoral zone, or the open-water pelagic zone.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatty acid analysis assumes that dietary lipids are broken down into their constituent fatty acids and incorporated relatively unchanged into consumer tissues (Howell et al., 2003; Iverson, 2009; Iverson et al., 2004), allowing spatial and temporal diet comparison among individuals (Duerksen et al., 2014; Eloranta et al., 2011; Hoffmann, 2017; Iverson, 2009; Scharnweber et al., 2016). Although internal regulation of fatty acids or biosynthesis is possible (Chaguaceda et al., 2020; Keva et al., 2019; Ruess & Müller‐Navarra, 2019), fatty acids have been assessed to be a robust tool to characterize lake trout diets (Happel et al., 2016, 2017). Thus, fatty acids were used as trophic bio‐indicators to better understand dietary patterns of piscivorous lake trout and investigate whether variation occurred among individuals in this ecotype and if individual specialization may be contributing to trophic patterns of this ecotype.…”
Section: Introductionmentioning
confidence: 99%